(untitled) (Lex Journal : Kajian Hukum dan Keadilan, 2018)
This article, entitled "ANNUAL LEAVE RIGHT ON WORKERS WITH PKWT (CONTRACT WORKERS)," writing on research methods used juridical normative, using the approach of the law (Statute Approach) and the conceptual approach (Conceptual Approach). The formulations of the problem in this paper are (1) What is a worker in Article 79 of Law No. 13 of 2003 required to have as a status as a permanent worker? and (2) What are the legal remedies that can be done for the contract worker/employee that does not get their annual leave entitlements? Resulting from the approach that the first formulation of the problem, the status of the workers mentioned in article 79 of Law No. 13 of 2003 on employment, do not have status as permanent workers, provided that an employee has worked for 12 consecutive months, the employee is entitled to receive annual leave entitlements. While in the second formulation of the problem, discuss the legal remedies that can be done by a worker if he does not get his annual leave entitlements. Workers can resolve the dispute at the Industrial Relations Settlement.